(Z)-Methyl 2-[(4-bromo-2-formylphenoxy)methyl]-3-o-tolylacrylate - Vijayakumar, S. (International Union of Crystallography, 2011)
In the title compound, C(19)H(17)BrO(4), the dihedral angle between the two benzene rings is 82.1 (1)°. The molecular structure is stabilized by an intramolecular C—H⋯O hydrogen bond which generates an S(7) ring motif. The crystal packing is stabilized by intermolecular C—H⋯O hydrogen bonds and C—H⋯π interactions. Intermolecular C—H⋯O interactions are involved in the formation of centrosymmetric R (2) (2)(16) dimers, which are connected into supramolecular tapes running along the [100] direction.